Evergreening in the Euro Area: Facts and explanation - Sven Steinkamp; Aaron Tornell; Frank Westermann (Osnabrück University, Institute of Empirical Economic Research, 2018)
Since the beginning of the financial crisis in 2007/8, new lending in the Euro-Area has slowed sharply and the old loans experienced "evergreening," i.e. bad loans have been rolled over rather than being liquidated. Even though ameliorating evergreening is key to promote lending for new investment projects and growth, no systematic evergreening measures exist. In this paper, we propose a new cross-country evergreening index and develop a model to explain why evergreening may reflect the incentives of regulators to forebear. Our evergreening index is based on a survey we designed, and was administered by the ifo institute to about 1,000 experts in over 80 countries. We bring the model to the data using a heteroscedastic probit model and find that evergreening is higher in: (i) Euro-Area countries than in the rest of the world; (ii) in countries facing bank distress; and (iii) is highest in countries which experience banking distress and are members of the Euro Area. These results are consistent with our theoretical model.
Keywords: F33; F55; E58; 330; Evergreening; Central bank credit; Survey data